Indium phosphide and black phosphorus employed surface plasmon resonance sensor for formalin detection: numerical analysis - Karki, Bhishma; Uniyal, Arun; Sharma, Tarun; Pal, Amrindra; Srivastava, Vivek (Optical engineering, 2022)
A hybrid Kretschmann configuration-based surface plasmon resonance biosensor is investigated to detect formalin in water was proposed. The modification is done in the conventional sensor by adding the indium phosphide (InP) and black phosphorus (BP) material layer. The silver (Ag) metal thickness is 45 nm, the optimized thickness of the metal for the proposed design. The thickness of the InP and BP materials 2 and 0.34 nm are considered. For three InP layers and one BP layer, the maximum sensitivity of 250.2  deg  /  RIU is achieved. The BP layer is used to improve the biorecognition ability of the sensor. The performance of the sensor is analyzed using the angular interrogation method. The proposed sensor is investigated for the aqueous sensing medium. The InP is an air-stable semiconductor material and has applications in chemical, medical, and biological fields.